An update on Ym1 and its immunoregulatory role in diseases - Kang, Qi; Li, Luyao; Pang, Yucheng; Zhu, Wenhua; Meng, Liesu (Frontiers in Immunology, 2022)
Ym1 is a rodent-specific chitinase-like protein (CLP) lacking catalytic activity, whose cellular origins are mainly macrophages, neutrophils and other cells. Although the detailed function of Ym1 remains poorly understood, Ym1 has been generally recognized as a fundamental feature of alternative activation of macrophages in mice and hence one of the prevalent detecting targets in macrophage phenotype distinguishment. Studies have pointed out that Ym1 may have regulatory effects, which are multifaceted and even contradictory, far more than just a mere marker. Allergic lung inflammation, parasite infection, autoimmune diseases, and central nervous system diseases have been found associations with Ym1 to varying degrees. Thus, insights into Ym1’s role in diseases would help us understand the pathogenesis of different diseases and clarify the genuine roles of CLPs in mammals. This review summarizes the information on Ym1 from the gene to its expression and regulation and focuses on the association between Ym1 and diseases.